2009
DOI: 10.22201/ib.20078706e.2009.003.158
|View full text |Cite
|
Sign up to set email alerts
|

Nematofauna asociada a la rizosfera de papas (Solanum tuberosum) cultivadas en la zona productora del Cofre de Perote, Veracruz, México

Abstract: Se determinaron y clasifi caron en grupos trófi cos las especies de nematodos asociados a la rizosfera de Solanum tuberosum en suelos altamente infectados por el nematodo dorado de la papa (Globodera rostochiensis) en un ciclo de cultivo, en la zona productora del Cofre de Perote, Veracruz, México. Se identifi caron 7 géneros (Aphelenchoides, Aphelenchus, Crassolabium, Mesodorylaimus, Plectus y Steinernema) y 8 especies (Aporcelaimellus obtusicaudatus, Ecumenicus monohystera, Acrobeles mariannae, Acrobeles sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
1
0
1
Order By: Relevance
“…G. rostochiensis was the only phytoparasitic nematode considered since in previous studies, it was shown to be the dominant species of potato crops in the study area (Desgarennes et al 2009). In each plot, the number of cysts, their contents (eggs and J2 per cyst), and emerged J2 juveniles extracted from the soil were quantified in order to estimate the infestation level of G. rostochiensis: (number of juveniles and eggs 100 ml soil −1 )0average cyst content× number of cysts+J2 100 ml soil −1 .…”
Section: Population Density Of G Rostochiensis and Free-living Nematmentioning
confidence: 94%
“…G. rostochiensis was the only phytoparasitic nematode considered since in previous studies, it was shown to be the dominant species of potato crops in the study area (Desgarennes et al 2009). In each plot, the number of cysts, their contents (eggs and J2 per cyst), and emerged J2 juveniles extracted from the soil were quantified in order to estimate the infestation level of G. rostochiensis: (number of juveniles and eggs 100 ml soil −1 )0average cyst content× number of cysts+J2 100 ml soil −1 .…”
Section: Population Density Of G Rostochiensis and Free-living Nematmentioning
confidence: 94%
“…Cruznema Artigas, 1927 es un género de nematodos bacteriófagos perteneciente a la familia Rhabditidae que suele estar asociado a cultivos, entre los que se pueden mencionar el ajo (Doucet, 1999), la papa (Desgarennes, 2009) 198,6 ± 8,02 (191-207), distancia del poro excretor al extremo anterior: 279 ± 9 (270-288), ancho medio: 102 ± 13,7 (90-117), ancho a nivel del ano: 62 ± 9,7 (36-81), longitud de la espícula: 49 ± 10,2 (27-63), ancho de la espícula: 9, longitud de la cola: 174,7 ± 35,2 (126-252) (ver Anexo, tabla 1).…”
Section: Comentariosunclassified